Sosialisasi: Peningkatan Motivasi Belajar bagi Siswa/i SMP Veteran Trisakti Mulyorejo - Nisa, Khairun; Afidatuzzaro, Nurul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research was conducted at the Trisakti Veterans Middle School, Mulyorejo. The purpose of writing this article is to explain the impact brought by KKM UIN Maulana Malik Ibrahim Malang when trying to increase the learning motivation of students thereby holding a socialization event with the theme “Socialization of Anti Mager Learning Motivation 2023” which took place on January 6, 2023, in the junior high school hall Veteran Trisakti, Mulyorejo. The authors found the fact that students in this junior high school have low to zero interest and motivation in learning. The socialization carried out was relatively simple but effective. The resource person provides interactive material so that students can interact during socialization. After conducting socialization, the author can see the direct impact felt by students at Trisakti Veterans Middle School. Basically, they become more motivated to learn. They also become aware of the problems that often hinder them in learning.